The Discursive Metonymy in the Imagery of American Folklore Ballads - Тетяна Суворова (Психолінгвістика, 2020)
Introduction. The article presents the effort to describe the semantics of American folklore ballads with account of the links between the images involved in the text creation. The discursive metonymy is considered to be the connecting cognitive mechanism of the ballad concepts that are objectified by the verbal images in the texts. Via the cognitive mechanism of the discursive metonymy the creative activity delivers understanding each text of the ballads as the unity of images presenting the definite creative idea.